(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
In the present day, ensuring student happiness has become a crucial priority for educational institutions, including schools and universities, necessitating continuous attention and improvement. The objective of this study is to establish a correlation between student happiness and the quality of educational services. 84 samples were gathered from several colleges in Ho Chi Minh City, Vietnam. The data collection was conducted using a quantitative technique and analyzed using SPSS software. The data indicate that student satisfaction is influenced by two factors: the competence of the lecturer and the evaluation of students.